Namma kāgadagaḷu Amērikā-Bhāratagaḷa siṃhāvalōkana - Kr̥ṣṇamūrti, Nāḍiga; Kr̥ṣṇamūrti, Nāḍiga; Guṇḍappanavaru, Ḍi. Vi (SAMP early 20th-century Indian books project, 1950)
Collection of author's correspondence with his friend, while in United States.